2021
DOI: 10.1001/jamaoto.2021.0715
|View full text |Cite
|
Sign up to set email alerts
|

Complications of COVID-19 Nasopharyngeal Swab Test

Abstract: During the COVID-19 pandemic, numerous swab samples have been taken for SARS-CoV-2 reverse transcriptasepolymerase chain reaction (RT-PCR) testing. Nasopharyngeal sampling is considered safe, despite adjacent vital structures (eg, orbit, skull base, rich vasculature; Figure). However, single case reports [1][2][3][4] and clinical observations indicate the possibility of severe complications. This case series investigated the frequency and type of SARS-CoV-2 nasopharyngeal test complications.Methods | All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 6 publications
0
58
0
1
Order By: Relevance
“…Overall, nasopharyngeal swabs are considered as a safe procedure, and complications are very rare. A study on more than 600,000 patients showed a complication rate of 1.24 per 100,000 performed SARS-CoV-2 tests, with the patient needing acute treatment in an emergency department [ 19 ]. Nose bleeding is the most common complication and should be kept in mind, especially if the swab meets resistance before 8 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, nasopharyngeal swabs are considered as a safe procedure, and complications are very rare. A study on more than 600,000 patients showed a complication rate of 1.24 per 100,000 performed SARS-CoV-2 tests, with the patient needing acute treatment in an emergency department [ 19 ]. Nose bleeding is the most common complication and should be kept in mind, especially if the swab meets resistance before 8 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Recent retrospectives reviews assessed the complications related to swab testing during the COVID-19 pandemic. Fabbris et al [ 2 ] found a low number of complications (0.16%), and Koskinen et al [ 10 ] reported an even lower rate (0.001%). Most were related to epistaxis (in some cases severe, requiring surgical procedures and blood transfusion) or broken swab impacted in the nasal cavity [ 2 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fabbris et al [ 2 ] found a low number of complications (0.16%), and Koskinen et al [ 10 ] reported an even lower rate (0.001%). Most were related to epistaxis (in some cases severe, requiring surgical procedures and blood transfusion) or broken swab impacted in the nasal cavity [ 2 , 10 ]. Other complications of nasal swabs have been described, such as nasal septum abscess, cerebrospinal fluid leak, and cribriform lamina fracture [ 2 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wrong trajectory of the applicator can also be hazardous to the nasal structures. Complication rates are low, and they are minor and self-limiting in most cases, but severe adverse events have also occurred, including liquorrhea [4,5,7,9,10,15]. Asthma and respiratory allergy prevalence is still increasing [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal (NPS) and oropharyngeal swabs (OPS) are the mainstays of sampling for either laboratory tests or point-of-care devices. Despite the significant number of tests performed, only few adverse events of swabbing have been reported [2][3][4][5][6][7][8][9][10][11]. Insertion of such applicators through natural orifices confers the possibility of foreign body retention with various consequences.…”
Section: Introductionmentioning
confidence: 99%